Romanul misterelor în literatura română a secolului al XIX-lea - o pagină de istorie literară uitată -: The mystery novel in the nineteenth-century Romanian literature – a forgotten piece of literary history – - Ursu, Manuela-Gabriela (Swedish Journal of Romanian Studies, 2022)
The following study looks into the history of a minimally studied Romanian literary form: the mystery novel. The particular aspects that define this subgenre are illustrated by the prose of Ioan M. Bujoreanu, entitled Mistere din București. The nineteenth-century Romanian literature is characterized by a tremendous expansion, particularly when we consider the general development of the novel. The first novels available in Romanian are translations from French literature, most of them very successful books belonging to the popular culture of that time. Following the French model, the Romanian authors created similar novels in which the most important elements were the extraordinary, the intrigue and the sensational situations that were meant to attract a very large public. Analyzing these numerous novels, most of them forgotten today, and trying to classify them we observe that the Romanian literary frame is very diverse. We can identify certain types such as the outlaw, the woman, the criminal or the mystery novel, all of them being eclectic proses. Of all the genres belonging to popular literature, the mystery novel stands out for its preoccupation and openness to illustrating the nineteenth-century social aspects. This type of novel succeeds to capture the literary style and the particular elements embedded in the first novelist writings. One of the most prominent writers who managed to incorporate an image of nineteenth-century society into his novel is Ioan M. Bujoreanu. He creates a very realistic scene of that time by observing the human condition, condemning the injustices of aristocrats against the Romanian peasants and closely describing the city of Bucharest down to the most minute detail. His novel demonstrates the importance of the mystery novel in the nineteenth-century Romanian popular writings which is a sociological one as well as a documentary one.